‘Who Can Refute a Sneer?’ Paley on Gibbon - Cole, Graham A. (Tyndale bulletin, 1998)
‘Who can refute a sneer?’ is a famous quotation from William Paley. It was his reaction to Edward Gibbon’s massive The Decline and Fall of the Roman Empire with its oblique, ironically delivered critique of Christianity. This article places the quotation in its context in Paley’s works and seeks to show how he addressed the sneer in his A View of the Evidences of Christianity in more than one place. In particular, Paley’s argument for the candour of the New Testament writers as evidence of their integrity (contra Gibbon) is examined and likewise his argument against the view that the rise of Islam is more impressive in some ways than that of Christianity (contra Gibbon). Paley’s response to David Hume’s writings has received some scholarly attention, but his response to Gibbon has been hardly explored. This article seeks to fill that lacuna.